Overexpression of the saccharopine dehydrogenase gene improves lysine biosynthesis in Flammulina velutipes. (18th July 2019) - Liu, Jianyu; Li, Qiaozhen; Jiang, Peiyu; Xu, Zhen; Zhang, Dan; Zhang, Lujun; Zhang, Meiyan; Yu, Hailong; Song, Chunyan; Tan, Qi; Shang, Xiaodong; Wang, Ruijuan
Abstract: Saccharopine dehydrogenase (EC 1.5.1.7) regulates the last step of fungal lysine biosynthesis. The gene ( Fvsdh ) encoding saccharopine dehydrogenase was identified and cloned from the whole genome of Flammulina velutipes . The genomic DNA of Fvsdh is 1257 bp, comprising three introns and four exons. The full‐length complementary DNA of Fvsdh comprises 1107 bp with a deduced amino acid sequence of 368 residues. A 1, 000‐bp promoter sequence containing the TATA box, CAAT box, and several putative cis ‐acting elements was also identified. The results of tissue expression analysis showed that the expression level of the Fvsdh gene was higher in the pileus than in the stipe whether in the elongation or maturation stage. Further research showed that the lysine contents were 3.03 and 2.95 mg/g in maturation‐pileus and elongation‐pileus, respectively. In contrast, the lysine contents were 2.49 and 2.07 mg/g in elongation‐stipe and maturation‐stipe, respectively. To study the function of Fvsdh, we overexpressed Fvsdh in F. velutipes and found that Fvsdh gene expression was increased from 1.1‐ to 3‐fold in randomly selected transgenic strains. The lysine contents were also increased from 1.12‐ to 1.3‐fold in these five transformants, except for strain T3, in which the lysine contents were the same as the control. These results indicate that the expression of the Fvsdh gene can affect the lysine content of F . velutipes .